Building Students' Social Emotional Character Phase A Through Project P5 Using Alternative Planting Media - Ambawono , Gancar Pramistri; Rahayuningsih, Setiti; Iswatiningsih, Daroe; Yudistira Fardana; Khasanah, Niswatun (Universitas Nusantara PGRI Kediri, 2025)
This study aims to measure the impact of planting activities using alternative planting media on the development of social-emotional character of Phase A students at SD Muhammadiyah 4 Malang City. The study used a quantitative approach with a quasi-experimental design. The research sample consisted of 130 grade 1 elementary school students involved in project-based activities. The research instruments in the form of questionnaires and structured observations were used to measure the development of aspects of cooperation, creativity, responsibility, and empathy. The results of the analysis showed that 5 students were in the